What role can minimum wages play in overcoming the low-wage model in central and eastern Europe? - Drahokoupil, Jan (Brussels, 2016)
"This working paper gives an overview of minimum wage policies in Central and Eastern Europe. It shows that minimum wages are an effective tool for reducing inequality by raising the lowest incomes. Minimum wages can have some, albeit limited, role in increasing aggregate productivity and promoting economic upgrading. However, to be truly effective in raising wages and productivity, minimum wages would need to be accompanied by a stronger role for collective bargaining in CEE countries."